Penelitian Stainless Steel 304 Terhadap Pengaruh Pengelasan Gas Tungsten Arc Welding (GTAW) Untuk Variasi Arus 50 A,100 A dan 160 A Dengan Uji Komposisi Kimia, Uji Struktur Mikro, Uji Kekerasan Dan Uji Impact - Setiawan, Ary; Ir. Pramuko Ilmu Proboputro, MT (2016)
The purpose of this study was to determine the percentage of the chemical composition of the stainless steel 304 and microstructure , hardness price , price impack stainless steel welds 304 to variations in air and water cooling. Materials studied are stainless steel series 304. The test object using a welding current of 50 A, 100 A and 160 A with a variation of that water and air conditioning . Tests performed are ; chemical composition testing , testing microstructure , hardness testing and impact testing. The test results are known chemical composition of the material type of austenitic stainless steel alloy Fe - Cr - Ni , levels of iron ( Fe ) = 71.45 % , chromium ( Cr ) = 18.12 % , nickel ( Ni ) = 8.49% , and manganese ( Mn ) = 0.914 , micro .Struktur didaapatkan austenite phase , ferrite and chromium carbides . 50 A specimen flow of air conditioning , air conditioning currents of 100 A , current 50 A water cooler and flows 160 a cooling water rather coarse grain structure and more chromium carbides . A flow of 160 specimens obtained air conditioning grain structure of the rudest and most forms chromium carbide . Hardness testing obtained an average price of violence lowest specimen on the specimen current of 100 A water cooler : welding Keywords : GTAW welding , stainless steel , air conditioners , water coolers